Kraft lignin ameliorates degradation resistance of starch in urea delivery biocomposites - Majeed, Z. (Elsevier Ltd, 2018)
Starch high biodegradation is a limitation for commercialization of starch derived slow release fertilizers (SRFs). To reduce starch biodegradation, kraft lignin (5â20) was tested for reducing the starch biodegradability in urea crosslinked starch (UcS) films, reported as here as a SRF. Biodegradability tests were conducted under anaerobic soil microcosm for period of 60 days. Fourier transformed infrared spectroscopy results showed an absence of peak at 1776 cmâ1 (pertained to oxidation of starch) in biodegraded lignin reinforced films. Thermogravimetric analysis of lignin reinforced films showed deceleration in the biodegradability rates, which were clearly evident from increase in the decomposition temperature at 5 weight loss, â¼67.0 Â°C and at maximum weight loss, â¼13.6 Â°C. Besides, char contents were increased, â¼11.3. Molecular weight distribution indicated the lignin's effect on conservation the molecular weight and polydispersity of starch in films. Lignin role in protecting the starch morphology was confirmed through optical microscopy results, which showed a less change for feret mean and particle area of starch particles. Further, lignin increased average roughness, â¼1.04 to 4.76 times for biodegraded films, possibly due to accumulation of lignin after loss of starch in films. Further, this study concluded that lignin influenced effectively the reduction in starch biodegradability under anaerobic soil microcosm. Thus, lignin could be used in urea crosslinked starch and other similar films, for controlling the starch biodegradability and improving the SRF formulations. Â© 2017 Elsevier Ltd